Athapaskan: a Structural Overview - Cook, Eung-Do (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1993)
AbstractIn this structural overview, I will focus on the morphology with a brief discussion of phonology and syntax for the reason that Athapaskan, as a "polysynthetic" language, has a very complex morphological structure of the verb. In terms of the number of segments, Athapaskan is one of the richest in the inventory of the consonants, which include three series of obstruents (plain, aspirated, and glottalized). Particularly rich is the inventory of affricates, which include, for most Athapaskan languages, three sets (dental, lateral, and palatal). The major lexical categories include verbs, nouns, and postpositions. Minor categories include deictic-demonstratives, numerals, locatives, adverbials, etc. Nouns and postpositions are morphologically identical in that they inflect with the same set of personal prefixes, marking a possessor for nouns and object for postpositions. But nouns and postpositions are different syntactically because only nouns function as a subject or direct object, whereas postpositions play other syntactic functions often incorporated into the verb. The verb morphology is characterized by a complex prefix structure as well as stem variation marking not only tense /aspect I mode, but also such other features as number and what are known to be the characteristics of the so-called 'classificatory' verbs. Athapaskan verbs are known for more or less a dozen prefix positions, although not all of these positions are filled for a particular verb. The classificatory verb system, which includes half a dozen or more alternating stems, is the most interesting and intriguing morphosemantic characteristic of the Athapaskan language, which would be particularly interesting to interpreters and translators. The syntactic structures involving the third and fourth person pronominal prefixes have been the most lively theoretical issue. Athapaskan is a verb-final language and a verb alone often represents a sentence. Typically the subject noun phrase and verb phrase are the first and last constituents of the sentence where other constituents, e.g. adverb, a postpositional phrase (indirect object) and direct object noun phrase occur between these two constituents. Relative clause and direct I indirect discourse are the best known noun phrase and verb phrase complementations, whereas topicalization and extraposition are the two best known movement rules in Athapaskan.